2014
DOI: 10.4028/www.scientific.net/amr.1000.285
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Impact-Echo Method for the Assessment of Long-Term Frost Resistance of Ceramic Tiles

Abstract: The aim of this paper is to evaluate the possibility of using the Impact-echo method for assessment of extremely long period of frost resistance of ceramic tiles. Sets of ceramic tiles of the Ia class to EN 14 411 B standard made by manufacture RACOs have been analyzed. The ceramic tiles under investigation have been subjected to 500 freeze-thaw-cycle based degradation in compliance with the relevant EN ISO 10545-12 standard. To verify the correctness of the Impact-echo method results, additional physical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The graph in Figure 4 demonstrates how the dominant frequency for each recorded AE hit shifts towards low values during freezing and thawing. This shift is caused by the mechanical wave passing through an increasingly more damaged environment [ 40 , 41 ]. It can be observed that during the first 25 F-T cycles, the dominant frequencies reach values around 200 kHz and as the number of F-T cycles increases, the dominant frequency decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The graph in Figure 4 demonstrates how the dominant frequency for each recorded AE hit shifts towards low values during freezing and thawing. This shift is caused by the mechanical wave passing through an increasingly more damaged environment [ 40 , 41 ]. It can be observed that during the first 25 F-T cycles, the dominant frequencies reach values around 200 kHz and as the number of F-T cycles increases, the dominant frequency decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The sensor is bee wax attached to the specimen under investigation. The recorded waveform of the signal is converted into a frequency spectrum by the Fast Fourier Transform [11,12].…”
Section: Impact-echo Methodsmentioning
confidence: 99%
“…Fig. 1 Typically AE signal [9] Even though many applications can be envisaged in all of the areas where composite materials are being used or could be used, it is surprising to see that the number of practical applications exploiting the AE technique has remained relatively limited [11]. The main reasons for this are the limitations of the analysis techniques discussed previously which make it difficult to extend laboratory results to industrial structures.…”
Section: Introductionmentioning
confidence: 99%